Post-Earthquake groundwater potential analysis in Mamuju Regency, West Sulawesi - Olyviani, Elsa; Priyono, Imam; Taufiq, Ahmad; Wardhana, Yan A.W.; Rinaldi, Dipta A.; Nugraha, A.M. Surya (Berita Sedimentologi, 2022)
The earthquakes that occurred in January 2021 at Mamuju, West Sulawesi not only caused damage to buildings but also destruction of water facilities. Thus, question is raised about the changes of groundwater quality in the area. This study aims to follow up this question by conducting the geoelectric measurement, pumping test, and water quality analysis. Based on the resistivity values of geoelectrical data, each area has aquifers in different stratigraphic layers of (1) calcareous sandstone of the Mamuju Formation, (2) lapilli rock of the Gunung Api Adang Formation, (3) breccia of the Gunung Api Adang Formation and (4) sandstone of the Alluvium deposit. These aquifers are mainly confined and were grouped into the shallow (less than 25 m deep) and deep (more than 25 m deep) aquifers. Water quality from the groundwater wells meet the criteria of Environmental Health Quality Standards, except for one well GL03-PLDA that has high manganese content. Determined discharge values suggest that water resources are enough to support around 3916 people or 999 settlements in Mamuju District and about 11664 people or 2916 settlements in Simboro District.